EXPLORING THE DYNAMICS OF TOURISM IN THE PHILIPPINES: OPPORTUNITIES AND CHALLENGES - B. Abari, Jeric; T. Malibiran, Leonora (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2024)
This paper examines the multifaceted aspects of tourism in the Philippines, a nation rich in cultural heritage and natural beauty, renowned for its diverse ecosystems, vibrant cultures, and hospitable people. With tourism contributing significantly to the country's economy, this study analyzes both the opportunities and challenges faced by the industry, particularly in the context of the COVID-19 pandemic, which drastically altered travel patterns. Employing a mixed-methods approach, including qualitative interviews and quantitative data analysis, the research highlights the implications of sustainability practices, cultural preservation, and community engagement in fostering a resilient tourism sector. The findings reveal that while the potential for growth remains high, addressing issues such as environmental degradation, over-tourism, and socio-economic disparities is critical for the future of Philippine tourism. This study aims to provide insights for policymakers, stakeholders, and researchers interested in sustainable tourism development in the Philippines.